Watershed impact evaluation using remote sensing - Kumar Gopal; Bagdi G L; Kurothe R S; Mishra P K; Pande V C; Rao B K; Sena D R; Vishwakarma A K (Current Science, 2014)
Watershed management is considered as a way for sustainable rural development and thus impact evaluation is a must. The common approach of post classification comparison of pre- and post-implementation satellite imageries for watershed impact evaluation suffers from serious limitations, mainly ignoring the changes which are not due to watershed interventions. To minimize such biases, control area approach is proposed and relative change in watershed compared to control area is attributed to watershed managment. The studied four clusters os watershed in Vidarbha region, Maharashtra show that the effect of the watershed could stand out irrespective of pre- and post-implimentation conditions of satellite imageries.
Keywords: Advantage watershed; Change detection; Impact evaluation; remote sensing; Watershed management